Metode PSSUQ dan UMUX dalam Usability Testing pada Website 21-23 Garden - Imam Rosyadi; Artanto, Fenilinas Adi; Nagara, Ikrar Stya; Nafilaturrosyidah, Farah (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
21-23 Garden is an MSME engaged in the buying and selling of plants, primarily indoor plants, and uses a website as an online sales tool. To maintain service quality, particularly on the 21-23 Garden website, a usability analysis is necessary. The Post Study System Usability Questionnaire (PSSUQ) and Usability Metric for User Experience (UMUX) methods are used to measure usability. The PSSUQ method evaluates usability by grouping four categories: system usefulness, information quality, interface quality, and overall satisfaction. The UMUX method targets usability by assessing effectiveness, efficiency, and user satisfaction. The PSSUQ analysis revealed complaints related to the speed of the shopping process, the completeness of product information, and the quality of the interface. The UMUX method, on the other hand, showed very positive results, with a UMUX score of 83.3, categorized as Very Good. These results indicate that the 21-23 website has good usability, but there are still challenges with the quality of the interface and the speed of the shopping process